STUDI KOORDINASI KERJA RELAI JARAK SEBAGAI PENGAMAN CADANGAN PADA SALURAN 150 KV GIS PESANGGARAN-GI NUSA DUA - Gusti, Deoka; Dyana Arjana, I Gede; Indra Partha, Cokorde Gede (Jurnal SPEKTRUM, 2021)
The development of Pesanggaran Conventional Substation into the Pesanggaran Gas Insulated Switchgear (GIS) as a form of increasing the reliability of the electric power system in Bali which led to changes in the protection system configuration on the transmission line connecting the GIS Pesanggaran and Nusa Dua Substation. The distance relay that was previously functioning as a primary protection was changed to backup protection due to the lack of selectivity of the distance relay in isolate the disruption and as the backup protection if the main protection experiencing a failure. Simulation testing using power system analysis software after determining the value of the distance relay setting and tested with short circuit at 110% and 180% of the transmission line length shows the distance relay has worked according to the P3B JB regulation No. 211/151/P3B/2010 and distance relay can detect disruption in zone 2 with a delay time of 0,815 seconds and detect disruption in zone 3 with a delay time of 1,615 seconds.